2017
DOI: 10.1590/0034-7167-2016-0476
|View full text |Cite
|
Sign up to set email alerts
|

Family resilience and chemical dependency: perception of mental health professionals

Abstract: Objective: To learn the perception of health professionals from the Psychosocial Attention Center for Alcohol and Other Drugs regarding the resilience attributes that are critical to family members of psychoactive substance dependents. Method: A qualitative descriptive study conducted from February to May 2016, using a focus group technique for data collection. In total, 15 professionals participated in the study: 13 health professionals and two administrative professionals. The statements were recorded and tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 13 publications
0
23
0
6
Order By: Relevance
“…Under such conditions, craving for drugs increases the temptation to relapse leading to abuse drugs (Davis et al 2018), whereas resiliency, as an internal and cognitive factor, can increase cognitive emotion regulation by developing better coping mechanisms and defensive strategies. Reduced resiliency when encountering life events makes the individual feel a type of mental pressure, anxiety, or depression (Zerbetto et al 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under such conditions, craving for drugs increases the temptation to relapse leading to abuse drugs (Davis et al 2018), whereas resiliency, as an internal and cognitive factor, can increase cognitive emotion regulation by developing better coping mechanisms and defensive strategies. Reduced resiliency when encountering life events makes the individual feel a type of mental pressure, anxiety, or depression (Zerbetto et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…With regard to the positive effect of resiliency on physical and mental health, some basic characteristics, such as being sociable, possessing problem-solving abilities, selfregulation, and having a sense of purpose and belief are emphasized. It has been reported that reduced resiliency against life events is accompanied by a sense of mental pressure, anxiety, or depression (Zerbetto et al 2017). The ability obtained by resilience allows the person to manage difficult and stressful life situations and paves the way for their development and positive balance.…”
Section: Discussionmentioning
confidence: 99%
“…Caregivers' experiences of emotional burdens caused feelings of confusion, anger, frustration, anxiety, depression, abandonment, anxiety, fear, embarrassment, and guilt [6]. Stigma also creates barriers for individuals with addictions, their families, and health care providers and can diminish the ability to seek and provide resources and support [28].…”
Section: Discussionmentioning
confidence: 99%
“…Families' resourcefulness demonstrated their determination to nd practical ways to meet theirs and their family's emotional and social needs [28]. These strategies provided encouragement and mutual learning opportunities for self-care.…”
Section: Discussionmentioning
confidence: 99%
“…These forces cover the family organization, through union towards the resolution of the problem, as well the belief in the hope of cure of its dependent relative and its perseverance in the treatment. 7 In the clinical practice of the family nursing, the nurses as they help the family in the acknowledgment and apprehension of their own positive forces, they potencialize and empower them. 8 These professionals, by potentializing, subsidizing and complimenting the strengths of the family, simultaneously, they instrumentalize it to discover existing resources and/or not yet acknowledge, as well as learning new competencies and skills or enhancement in the process of the family relationships.…”
Section: Introductionmentioning
confidence: 99%